Intersectionality in higher education research: a systematic literature review. Issue 6 (19th September 2019) - Nichols, Sue; Stahl, Garth
ABSTRACT: This paper presents a systematic structured review of recent research that explicitly adopts intersectionality as a theoretical framework to interrogate how tertiary institutions manage, cater for, include, exclude and are experienced in ways that produce advantage and disadvantage. The analysis addresses the following questions: Within research that uses intersectionality, what aspects of the HE context are the focus? What methodologies are employed and how do these contribute to the production of knowledge? What vectors of identity are included? We find that gender appeared as the primary identity with which other dimensions of difference were combined to produce intersectional positions. Furthermore, case study and auto-ethnographic designs were primary approaches. This systematic literature review of 50 papers demonstrates that, when considering the workings of multiple systems of (dis)advantage, academic participation is intertwined with social and personal aspects of the HE experience. While intersectionality challenges the dominant instrumental view of HE, our review concludes that there is considerable work to be done to actively address the workings of intersecting systems of inequity impacting on participation and outcomes of students and faculty.